Designing Model and Levelization of the Factors Affecting Companies’ Green Financing through Banking System - Abbasali Sheikh; Parviz Saeidi; Ebrahim Abbasi; Arash Naderian (Iranian Journal of Accounting, Auditing & Finance)
Creating businesses compatible with the environment and providing competitive advantages for companies. Banks are vital in creating ecological balance through economic growth and development of this type of entrepreneurship by considering the environmental risks through the companies’ green financing. Taking into account the importance of the proper financing method in accomplishing the ideas of environmental entrepreneurs, the present research aimed to model the components affecting companies' green financing through the state banking system. This is mixed-method research. The first part included Grounded Theory (GT) and interviews with 36 experts selected through purposive and snowball sampling. After extracting 362 open codes, 77 subsidiary components and 21 principal components were identified. In the second part, 20 components with the highest code frequency were included, and by employing the interpretive structural modeling (ISM), the components’ relationship and sequences were classified into 6 levels. The results of MICMAC analysis revealed that components of understanding the conditions and requirements of green projects plus setting green goals for the banks concerning their mission are pretty effective in implementing green financing as a crucial factor in accomplishing sustainable entrepreneurship and the emergence of clean industries.